IMPROVING DELIBERATIONS BY REDUCING MISREPRESENTATION EFFECTS. (December 2020) - Imbert, Cyrille; Boyer-Kassem, Thomas; Chevrier, Vincent; Bourjot, Christine
ABSTRACT: Deliberative and decisional groups play crucial roles in most aspects of social life. But it is not obvious how to organize these groups and various socio-cognitive mechanisms can spoil debates and decisions. In this paper we focus on one such important mechanism: the misrepresentation of views, i.e. when agents express views that are aligned with those already expressed, and which differ from their private opinions. We introduce a model to analyze the extent to which this behavioral pattern can warp deliberations and distort the decisions that are finally taken. We identify types of situations in which misrepresentation can have major effects and investigate how to reduce these effects by adopting appropriate deliberative procedures. We discuss the beneficial effects of (i) holding a sufficient number of rounds of expression of views; (ii) choosing an appropriate order of speech, typically a random one; (iii) rendering the deliberation dissenter-friendly; (iv) having agents express fined-grained views. These applicable procedures help improve deliberations because they dampen conformist behavior, give epistemic minorities more opportunities to be heard, and reduce the number of cases in which an inadequate consensus or majority develops.